2014
DOI: 10.1093/neuonc/nou236
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor and variant III targeted immunotherapy

Abstract: Immunotherapeutic approaches to cancer have shown remarkable promise. A critical barrier to successfully executing such immune-mediated interventions is the selection of safe yet immunogenic targets. As patient deaths have occurred when tumor-associated antigens shared by normal tissue have been targeted by strong cellular immunotherapeutic platforms, route of delivery, target selection and the immune-mediated approach undertaken must work together to maximize efficacy with safety. Selected tumor-specific targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Previous studies have indicated that a high expression level of EGFRvIII is positively correlated with the invasion abilities of GBM cells. Previous studies have also indicated that 30–60% of GBM patients exhibit high expression levels of EGFRvIII, and these mutations are not detected in normal brain tissues of adult humans or other normal tissues ( 17 19 ). Therefore, EGFRvIII is a good target for GBM gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that a high expression level of EGFRvIII is positively correlated with the invasion abilities of GBM cells. Previous studies have also indicated that 30–60% of GBM patients exhibit high expression levels of EGFRvIII, and these mutations are not detected in normal brain tissues of adult humans or other normal tissues ( 17 19 ). Therefore, EGFRvIII is a good target for GBM gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In gliomas, the variant III of the epidermal growth factor receptor (EGFRvIII), which results from an in-frame intragenic deletion of EGFR exons 2-7, is present in approximately 20% to 30% of glioblastomas and a recognized target in many peptide vaccination studies [21][22][23]. A peptide vaccine targeting EGFRvIII (rindopepimut) displayed evidence for immunogenicity and efficacy in early phase trials for EGFRvIII+ glioblastoma patients [24][25][26][27].…”
Section: Peptide Vaccination Trialsmentioning
confidence: 99%
“…EGFRvIII is detected in approximately 20% to 30% of glioblastoma samples, and in general is coexpressed with the wild-type variant on a single-cell level. 42 A peptide vaccine conjugated to the adjuvant keyhole limpet hemocyanin (KLH) induces robust anti-EGFRvIII antibody responses in patients with EGFRvIII-positive tumors. 43 After encouraging results from noncontrolled phase I/II studies, the randomized ACT-IV registration trial, tested the efficacy of EGFRvIII Pep-KLH (rindopepimut) compared with placebo when combined with temozolomide radiochemotherapy in patients with newly diagnosed EGFRvIII-positive glioblastoma (NCT01480479).…”
Section: Vaccination Strategiesmentioning
confidence: 99%